Percutaneous closure of patent ductus arteriosus in interrupted inferior caval vein through femoral vein approach - Endale Tefera; Ramon Bermudez-Cañete (Wolters Kluwer Medknow Publications, 2014)
Percutaneous closure of the patent arterial duct in patients with interrupted inferior caval vein poses a technical challenge. A 12-year-old girl with a patent ductus arteriosus (PDA) and interrupted inferior caval vein is described in this report. The diagnosis of interrupted inferior caval vein and azygos continuation was made in the catheterization laboratory. A catheter was advanced and snared in the descending aorta. An exchange wire was advanced through the catheter and snared in the descending aorta. Then, an Amplatzer TorqVue 2 delivery sheath was advanced over the wire from the venous side and again snared in the descending aorta. An Amplatzer duct occluder (ADO) size 8/6 was advanced through the sheath while still holding the sheath with a snare. The device was opened. The sheath was then unsnared once the aortic disc was completely out. The sheath and the device were pulled back into the duct and the device was successfully implanted. The device was then released and it attained a stable position. An aortic angiogram was performed which showed complete occlusion.